Sniffing out significant "Pee values": genome wide association study of asparagus anosmia. (13th December 2016) - Markt, Sarah C; Nuttall, Elizabeth; Turman, Constance; Sinnott, Jennifer; Rimm, Eric B; Ecsedy, Ethan; Unger, Robert H; Fall, Katja; Finn, Stephen; Jensen, Majken K; Rider, Jennifer R; Kraft, Peter; et al.
Abstract : Objective  To determine the inherited factors associated with the ability to smell asparagus metabolites in urine. Design  Genome wide association study. Setting  Nurses' Health Study and Health Professionals Follow-up Study cohorts. Participants  6909 men and women of European-American descent with available genetic data from genome wide association studies. Main outcome measure  Participants were characterized as asparagus smellers if they strongly agreed with the prompt "after eating asparagus, you notice a strong characteristic odor in your urine, " and anosmic if otherwise. We calculated per-allele estimates of asparagus anosmia for about nine million single nucleotide polymorphisms using logistic regression. P values <5×10 -8 were considered as genome wide significant. Results  58.0% of men (n=1449/2500) and 61.5% of women (n=2712/4409) had anosmia. 871 single nucleotide polymorphisms reached genome wide significance for asparagus anosmia, all in a region on chromosome 1 (1q44: 248139851-248595299) containing multiple genes in the olfactory receptor 2 ( OR2 ) family. Conditional analyses revealed three independent markers associated with asparagus anosmia: rs13373863, rs71538191, and rs6689553. Conclusion  A large proportion of people have asparagus anosmia. Genetic variation near multiple olfactory receptor genes is associated with the ability of an individual to smell the metabolites of asparagus in urine. Future replication studies are necessary before considering targeted therapies to help anosmic people discover what they are missing.